The contribution of principal transformational leadership and work commitment to the innovative behaviour of civil servant teachers - Variani, Herlin; Nellitawati; Sabandi, Ahmad; Sufyarma (Indonesian Research Journal in Education |IRJE|, 2025)
Abstract This research aimed to examine the contribution of transformational leadership to innovative behaviour, the contribution of work commitment to innovative behaviour, and the contribution of transformational leadership and work commitment to the innovative behaviour of public elementary school teachers in Sijunjung Regency. This research used a quantitative research design with a population of 92 teachers. The sample was taken using stratified proportional random sampling, with 20 teachers. The research instrument was a questionnaire. The results of the data analysis showed that transformational leadership significantly contributed to the innovative behaviour of public elementary school teachers in Sijunjung Regency by 45%, and work commitment significantly contributed to the innovative behaviour of public elementary school teachers in Sijunjung Regency by 20.5%. Transformational leadership and work commitment significantly contributed to the innovative behaviour of public elementary school teachers in Sijunjung Regency by 20.5%. The data support the hypothesis, and transformational leadership and work commitment are two important factors that help State Elementary School teachers in Sijunjung Regency be more innovative; other factors account for the remaining 79.5%.